PENGARUH TAX AVOIDANCE, MANAJEMEN LABA, KOMISARIS INDEPENDEN, DAN KOMITE AUDIT - Nurcahyono, Nurcahyono (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2021)
The purpose of this study is to analyze and empirically prove the factors that affect firm value. This study uses a quantitative approach to the type of comparative causal research. The population of this research is property, real estate, and construction listed on the Indonesia Stock Exchange in 2015-2019 the sampling technique used is purposive sampling. Data analysis used multiple linear regression analysis. The results of this study indicate that tax avoidance and earnings management have a positive effect on firm value, this indicates that companies that engage in tax avoidance and earnings management display an ostensibly high profit, thus attracting many investors and the impact on the value of the company increases. Independent commissioners and audit committees have a positive effect on firm value, this indicates that the good corporate governance mechanism with independent commissioners and audit committees that play an effective role in the company will increase firm value.